A role for the alpha-8 integrin chain (itga8) in glomerular homeostasis of the kidney. - Marek, Ines; Hilgers, Karl Friedrich; Rascher, Wolfgang; Wölfle, Joachim; Hartner, Andrea (Molecular and Cellular Pediatrics, 2020)
Glomerulonephritis results in a dysregulation of glomerular cells and may end up in chronic alterations and subsequent loss of renal function. Therefore, understanding mechanisms, which contribute to maintain glomerular integrity, is a pivotal prerequisite for therapeutic interventions. The alpha-8 integrin chain seems to be an important player to maintain glomerular homeostasis by conferring mechanical stability and functional support for the renal capillary tuft.
EVALuna2:383426
Keywords: itga8; Glomerular homeostasis; Mesangial cells; Glomerulonephritis